Static removal of copper (ii) from aqueous solutions by hematite - Chakravarty R.; Prasad G.; Raupainwar D.C. (My University, 2025)
This study examines the adsorption characteristics for the removal of copper (II) from aqueous solution using natural hematite which is available in abundance in this country. The static characterisation of the kinetics of the adsorption process has been studied using batch experiments at different adsorbate/adsorbent ratios for pH for fixed ionic strength. Adsorption isotherms have been modelled with the help of both Langmuir and Freundlich formulae. The dependence of the adsorption of the metal ion on the pH of the solution has been studied to achieve a better understanding of the adsorption mechanism. It has been found that maximum adsorption of Cu(II) from aqueous solution takes place at a pH value of 8.0. It has been concluded that the adsorption process comprises monolayer adsorption followed by intraparticle diffusion. © 1998 Taylor & Francis Group, LLC.